Simultaneous Determination of Original, Degraded Ginsenosides and Aglycones by Ultra High Performance Liquid Chromatography Coupled with Quadrupole Time-of-Flight Mass Spectrometry for Quantitative Evaluation of Du-Shen-Tang, the Decoction of Ginseng - Shan-Shan Zhou; Jin-Di Xu; He Zhu; Hong Shen; Jun Xu; Qian Mao; Song-Lin Li; Ru Yan (Molecules, 2014)
In the present study, an ultra-high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-QTOF-MS) method for simultaneous determination of eleven original, fourteen degraded ginsenosides and five aglycones was developed and validated to quantitatively evaluate the transformation of ginsenosides during preparation of Du-Shen-Tang, the decoction of ginseng. Both positive and negative modes as well as the step wave ion transfer optics technology were used to increase the detection sensitivity of QTOF-MS. The extracting ion mode based on the quasi-molecular ions, molecular ions and fragment ions characteristic to each analyte was used to increase the selectivity for quantitative analysis. Under the optimized UHPLC and QTOF-MS conditions, the 30 analytes with different polarities were separated (except for Re and Rg1) within 26 min. The developed method was applied for the quantitative comparison of Du-Shen-Tang and its raw materials derived from Asian ginseng (ASG) and American ginseng (AMG), respectively. It was found that the contents of the original ginsenosides decreased from 26,053.09 to 19,393.29 μg/g or 45,027.72 to 41,865.39 μg/g, whereas the degraded ginsenosides and aglycones increased from 159.72 to 685.37 μg/g or 676.54 to 1,502.26 μg/g in Du-Shen-Tang samples of ASG or AMG when compared with their raw materials, indicating that decocting could dramatically increase the proportion of the less polar degraded ginsenosides in Du-Shen-Tang. Whether these changed proportions of different polar ginsenosides could affect the bioactivities of the decoctions and their raw materials derived from ASG and AMG deserves further investigation.